Mange - P.G. Koehler; A. Chaskopoulou (EDIS, 2011)
This document provides an overview of mange, a skin condition caused by burrowing mites. It describes the types of mange affecting various animals, including dogs, cats, and humans, and details the symptoms, life cycle, and transmission methods of mange mites. The document emphasizes the importance of veterinary treatment and proper hygiene to prevent and manage mange. It also discusses specific types of mange, such as sarcoptic, demodectic, and ear mange, highlighting their unique characteristics and treatment options. Publication date: February 1993.